SP110 Polymorphisms Are Genetic Markers for Vulnerability to Latent and Active Tuberculosis Infection in Taiwan. (5th December 2018) - Chang, So-Yi; Chen, Mei-Ling; Lee, Meng-Rui; Liang, Yun-Chieh; Lu, Tzu-Pin; Wang, Jann-Yuan; Yan, Bo-Shiun
Abstract : One-fourth of the human population is estimated to have been exposed to Mycobacterium tuberculosis ( Mtb ) and carries the infection in its latent form. This latent infection presents a lifelong risk of developing active tuberculosis (TB) disease, and persons with latent TB infection (LTBI) are significant contributors to the pool of active TB cases. Genetic polymorphisms among hosts have been shown to contribute to the outcome of Mtb infection. The SP110 gene, which encodes an interferon-induced nuclear protein, has been shown to control host innate immunity to Mtb infection. In this study, we provide experimental data demonstrating the ability of the gene to control genetic susceptibility to latent and active TB infection. Genetic variants of the SP110 gene were investigated in the Taiwanese population (including 301 pulmonary TB patients, 68 LTBI individuals, and 278 healthy household contacts of the TB patients), and their association with susceptibility to latent and active TB infection was examined by performing an association analysis in a case-control study. We identified several SNPs (rs7580900, rs7580912, rs9061, rs11556887, and rs2241525) in the SP110 gene that are associated with susceptibility to LTBI and/or TB disease. Our studies further showed that the same SNPs may have opposite effects on the control of susceptibility to LTBI versus TB. In addition, our analyses demonstrated that the SP110 rs9061 SNP was associated with tumor necrosis factor- α (TNF α ) levels in plasma in LTBI subjects. The results suggest that the polymorphisms within SP110 have a role in controlling genetic susceptibility to latent and active TB infection in humans. To the best of our knowledge, this is the first report showing that the SP110 variants are associated with susceptibility to LTBI. Our study also demonstrated that the identified SP110 SNPs displayed the potential to predict the risk of LTBI and subsequent TB progression in Taiwan.